Una narrativa fallida: Holocausto, humor y denuncia ante la última dictadura cívico-militar argentina - Laura Schenquer (Centre de Recherches sur les Mondes Américains, 2014)
This article will explore two events: the first one that took place in October 1979, under the argentinian last dictatorship regime; and the second one occurred later, in April 1984, in the first months of democracy. The common thread among them was to have promoted the placement of the Holocaust (the term used to call the Nazi’s genocide of the Jewish population, that became the symbol or most important reference of the persecution and violence organized by the State) to refer critically to the military dictatorship in Argentina. However, none of these attempts succeeded in its mission. They were questioned and hampered, and so they failed as metaphors of the situation of terror and repression. The interesting thing is that it was not the state censorship during the dictatorship neither it was the democracy official discourse that limited these actions but, as we will show, were another civil actors who opposed. Our hypothesis is these actors acted according to their logical and traditional principles that determined the same behavior during different periods, while other actors used the Holocaust to make sense of what they conceived as a critical time.